KEPENTINGAN INDONESIA BEKERJASAMA DENGAN SPANYOL DALAM BIDANG PERTAHANAN DAN MILITER TAHUN 2013 - Putra, Reza Ramandra; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study analyzes the factors that motivate Indonesia signed a cooperative relationship with Spain in the fields of defense and military in 2013. The reasons which prompted Indonesia to cooperate with Spain and the benefits to be gained by Indonesia. The study also will explain the process from the beginning and cooperative relations between Indonesia and Spain on defense and military aircraft industry that has been initiated in 2007, by the two countries.Keywords : cooperative relationship, process, reasons, aircraft industry.